One-step synthesis of a robust, ultrathin, stretchable antifogging copolymer film. Issue 13 (28th February 2023) - Ryu, Jin; Oh, Myung Seok; Yoon, Jongsun; Kang, Minjeong; You, Jae Bem; Lee, Hyomin; Im, Sung Gap
Abstract : A conformal antifogging polymer thin film with high stretchability was synthesized in a one-step manner using a vapor phase method. Abstract : Recent advances in wearable and embeddable displays have led to an increase in demand for functional coatings that are stretchable and also retain high optical transparency in fogging conditions. Herein, a conformal antifogging polymer thin film with exceptional stretchability was synthesized in a one-step manner using initiated chemical vapor deposition (iCVD). A series of polymer films were generated by copolymerization of a soft, hydrophilic 2-hydroxyethyl acrylate (HEA) together with a small fraction of a crosslinker 1, 3, 5-trivinyl-1, 3, 5-trimethylcyclotrisiloxane (V3D3). The composition of the film was precisely adjusted by controlling the flow rates of the input monomers in the vapor-phase deposition process to yield conformal hydrophilic antifogging films. Unlike conventional antifogging films that often lack mechanical durability due to excessive swelling, the iCVD-based antifogging polymer film offers the means to modulate the extent of crosslinking to achieve an excellent antifogging performance while imparting high elasticity with an elastic limit exceeding 300%. Detailed investigation of the antifogging performance and the mechanical properties through repeated cyclic stress–strain tests on sets of films with different compositions revealed that, in comparison to the commercial antifogging spray coating, the optimal iCVD-based antifogging copolymer film (pH8V1) maintains a high transmittance (>99%) upon exposure to hot water vapor, in the cold-fog transition test, and even in a stretched state.